Peculiarities of correcting load parameters in power training of mixed martial arts athletes - Chernozub, A.; Danylchenko, S.; Imas, Y.; Eichina, M.; Ieremenko, N.; Korobeynikov, G.; Korobeynikova, L.; Potop, V.; Cynarski, W. C.; Gorashchenco, A. (Journal of Physical Education and Sport, 2019)
Purpose: to identify the optimal load parameters in the process of power training of Mixed Martial Arts athletes with a wrestling style on the basis of studying adaptive and compensatory body reactions in conditions of intense muscular activity of different intensity and volume of work.Material: We examined 40 sportsmen aged (21 ± 0.8), who participated in Mixed Martial Arts fights during the last (2.0 ± 0.3) years and used predominantly a wrestling style of fighting. The athletes were divided into 2 groups: group A and B. The participants of group A used the low-intensity load and the large amount of work in the training process. Athletes of group B used loads of high intensity and small volume of work. Morphometric, biochemical, and statistical methods of research were used to study the features of adaptive and compensatory body reactions of these athletes in conditions of power training of different intensity. Results: The obtained results show that athletes of group A increased their circumference indices by 1.9% on average after 3 months of research. In group B, for the same period of time, the studied indices increased by 5.5% on average compared to the baseline data. It was noted that at the beginning of the study, the cortisol concentration in blood serum of group A athletes decreased after exercises by 23.9% in comparison with the basal ones. This fact indicates compensatory reactions to the stimulus and high energy costs. We observed completely opposite changes in group B sportsmen. They were expressed in the increase of the studied indicator by 46% in comparison with the data recorded before exercises. This fact testifies to the adequacy of the loads to the functional body capabilities of this group of athletes. The results of biochemical control of the changes in the hormone testosterone and the enzyme lactate dehydrogenase in the blood of both groups` athletes confirm the fact that it is the use of high-intensity loads that promotes the enhancement of the athletes' adaptive body capabilities for training activities in MMA. Conclusions: The analysis of the results obtained during the series of experimental studies indicates the necessity of correcting load parameters during power training. It should be based on the analysis of athletes` adaptive and compensatory body reactions to a stress stimulus. Otherwise there should be developed completely new training programs.